Education and the public's desire for social distance from people with depression and schizophrenia: The contribution of emotional reactions and causal attributions. (August 2014) - von dem Knesebeck, Olaf; Angermeyer, Matthias C; Kofahl, Christopher; Makowski, Anna Christin; Mnich, Eva
Background: Association between education and desire for social distance from people with mental illness is unclear. Aims: (1) Is there an association between education and social distance from people with a depression or schizophrenia? (2) Can this association be explained by beliefs about causes of and emotional reactions to the mental disorders? (3) Are there differences between the two mental disorders? Methods: Analyses are based on a telephone survey in two large German cities (Hamburg and Munich, N = 2, 014, response rate 51%). Vignettes with typical signs and symptoms suggestive of depression and schizophrenia were presented. Respondents were asked about beliefs about causes of the mental disorders, their emotional reactions and their desire for social distance. Results: Lower education is significantly associated with a stronger tendency for social distance in the case of depression but not in case of schizophrenia, when age and gender are controlled. In case of depression, the association decreases when beliefs about possible causes are additionally controlled. In terms of schizophrenia, associations between education and social distance become stronger when emotional reactions are introduced. Conclusions: Our results underline that campaigns aimed at reducing stigma and social distance should consider specific emotional reactions and information needs of people with low education regarding different mental disorders.